Karakteristik Kejadian Ikutan Pasca Vaksinasi Covid-19 Pada Tenaga Kesehatan Pada Masa Pandemi Covid-19 - YulAfni (Jurnal Ilmiah Cerebral Medika, 2021)
The world is faced with the Covid-19 pandemic, the Government of Indonesia has declared the Covid-19 pandemic a National disaster, many efforts have been made by the government to suppress the transmission of the Covid-19 virus, but it seems that Covid-19 is reluctant to leave so that it develops by bringing up a new variant, namely Omicron, Health workers are the front line in providing health services during the COVID-19 pandemic. The purpose of the study was to describe the characteristics of post-vaccination adverse events in health workers who received the Covid-19 vaccination as an effort to anticipate the transmission of Covid-19 from the Omicron variant at Reksodiwiryo Hospital, Padang. Method The research design was a descriptive study with a cross-sectional method. The research subjects were 35 nurses who had received the covid-19 vaccine. This research was carried out directly with a questionnaire while still complying with health protocols. This research was conducted in October 2021. The data collection technique used in this study was Acidental-sampling. Results Characteristics of the age of the respondents, the majority of respondents aged 24-30 years as many as 19 (54.3%), The majority of respondents had no previous medical history as many as 20 (57.2%), The incidence of AEFIs in the majority of respondents after the Covid-19 vaccine was none 25 ( 71.4%), The majority of respondents showed fever after the vaccine did not exist as many as 25 (71.4%), The majority of respondents based on the incidence of AEFI after the Covid-19 vaccine appeared diarrhea was not 25 respondents (71.4%), The majority of respondents appeared shortness of breath there were 25 respondents (71.4%) Conclusion Characteristics of the emergence of AEFI in respondents who received the Covid-19 vaccination based on age, sex, past medical history, number of AEFI incidents, and very minimal types of AEFI symptoms